A new hemodynamic index to predict late right failure in patients implanted with last generation centrifugal pump. Issue 7 (19th April 2021) - Montalto, Andrea; Amarelli, Cristiano; Piazza, Vito; Hopkins, Kali; Comisso, Marina; Pantanella, Romina; Musumeci, Francesco
Abstract: Background: Right ventricular failure (RVF) is a severe event that increases perioperative mortality after left ventricle assist device (LVAD) implantation. Right ventricular (RV) function is particularly affected by the LVAD speed by altering RV preload and afterload as well as the position of the interventricular septum. However, there are no studies focusing on the relationship between pump speed optimization and risk factors for the development of late RVF. Methods: Between 2015 and 2019, 50 patients received LVAD implantation at San Camillo Hospital in Rome. Of these, 38 who underwent pump speed optimization were included. Post‐optimization hemodynamic data were collected. We assessed a new Hemodynamic Index (HI), calculated as follows:  HI = MAP × PCWP CVP × RPM set RPM max,  to determine the risk of late RVF, which was defined as the requirement for rehospitalization and inotropic support. Results: Ten patients had late RVF after LVAD implantation. Five patients required diuretic therapy and speed optimization. Three patients required inotropic support with adrenaline 0.05 μg/kg/min. Two patients needed prolonged continuous venovenous hemofiltration and high dose inotropic support. Multivariate analysis revealed that a low HI (odds ratio 11.5, 95% confidence interval, 1.85–65.5, p  [.003]) was an independent risk factor for late RVF after LVAD implantation. Conclusion: We demonstrated a low HI being a significant risk factor for the development of RVF after LVAD implantation. We suggest implementing HI as a decision support tool for goal‐direct optimization of the device aiming to reduce the burden of late‐onset RVF during the follow‐up.